Pola pengasuhan 1.000 hari pertama kehidupan dan status gizi anak bawah dua tahun (baduta) di Kota Medan - Yuly Astuti; Widayatun Widayatun (Jurnal Kependudukan Indonesia, 2021)
Health problems in the first 1000 days of life have short- and long-term consequences for children under the age of two years. This study examines how the childcare pattern during the first 1000 days of life affects the nutrition status of children under two in Medan City. This study is conducted by using mixed methods approach. A survey was performed to collect quantitative data of 400 households in 20 urban villages, whereas in-depth interviews and focus group discussions were conducted to collect qualitative data. In this study, childcare during the first 1000 days of life includes colostrum feeding, early initiation of breastfeeding, exclusive breastfeeding, and complementary feeding practices. The study’s findings show that mothers’ education level is significantly associated to their knowledge of colostrum's benefit. Support from health providers and room-in policy needs to be improved to increase early initiation breastfeeding and exclusive breastfeeding. Additionally, mothers have even more variety of complementary feeding for children aged 6–24 months due to cultural practices and tradition. Thus, improving children under two’s nutrition status requires comprehensive health promotion by considering sociocultural factors and evaluating the implementation of policies that support early initiation breastfeeding and exclusive breastfeeding practices.